2021
DOI: 10.3389/fcimb.2021.664221
|View full text |Cite
|
Sign up to set email alerts
|

The Active Subunit of the Cytolethal Distending Toxin, CdtB, Derived From Both Haemophilus ducreyi and Campylobacter jejuni Exhibits Potent Phosphatidylinositol-3,4,5-Triphosphate Phosphatase Activity

Abstract: Human lymphocytes exposed to Aggregatibacter actinomycetemcomitans (Aa) cytolethal distending toxin (Cdt) undergo cell cycle arrest and apoptosis. In previous studies, we demonstrated that the active Cdt subunit, CdtB, is a potent phosphatidylinositol (PI) 3,4,5-triphosphate phosphatase. Moreover, AaCdt-treated cells exhibit evidence of PI-3-kinase (PI-3K) signaling blockade characterized by reduced levels of PIP3, pAkt, and pGSK3β. We have also demonstrated that PI-3K blockade is a requisite of AaCdt-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 60 publications
1
14
1
Order By: Relevance
“…As noted earlier, several investigators have reported that Cdt-treated cells exhibit DDR activation exemplified by phosphorylation of H2AX; these findings have also been interpreted as indirect evidence of toxin-induced DNA damage due to CdtB-associated DNase activity [ 68 , 69 , 70 ]. However, we, and others, have demonstrated that the DDR is not activated (i.e., we do not observe increases in pH2AX) in lymphocytes under conditions of Cdt-treatment that involve exposure to optimal levels of toxin required to induce both cell cycle arrest and apoptosis [ 15 , 45 , 47 , 51 ]. Higher doses of toxin nominally increased pH2AX levels; however, these increases appeared to be the result of activation of the apoptotic cascade rather than a direct effect of Cdt on DNA damage [ 51 ].…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…As noted earlier, several investigators have reported that Cdt-treated cells exhibit DDR activation exemplified by phosphorylation of H2AX; these findings have also been interpreted as indirect evidence of toxin-induced DNA damage due to CdtB-associated DNase activity [ 68 , 69 , 70 ]. However, we, and others, have demonstrated that the DDR is not activated (i.e., we do not observe increases in pH2AX) in lymphocytes under conditions of Cdt-treatment that involve exposure to optimal levels of toxin required to induce both cell cycle arrest and apoptosis [ 15 , 45 , 47 , 51 ]. Higher doses of toxin nominally increased pH2AX levels; however, these increases appeared to be the result of activation of the apoptotic cascade rather than a direct effect of Cdt on DNA damage [ 51 ].…”
Section: Discussioncontrasting
confidence: 61%
“…Exposure to Cdt not only leads to decreases in pGSK3β and, in turn, kinase activation, but we have also shown that Cdt’s toxicity on other cell types was dependent upon activation of this kinase [ 24 , 42 , 47 ]. As shown in Figure 6 B, TIGK cells exposed to Cdt alone (blue bars), exhibited cell cycle arrest as the percentage of G2/M cells was significantly increased over control cell (no Cdt) values.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…revealed that A. actinomycetemcomitans CDT-treated macrophages exhibited GSDMD-mediated pyroptosis for its phosphatidylinositol-3,4,5-trisphosphate (PIP 3 ) phosphatase activity ( Shenker et al., 2020 ). Recently, PIP 3 phosphatase activity of C. jejuni CDT was discovered ( Huang et al., 2021 ). In the present study, however, no relationship was found between GSDMD and C. jejuni CDT-induced pyroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…CdtB has been known for a while to function as type I deoxyribonuclease (DNAse I) that cleaves double stranded DNA within host cells [ 126 , 127 ]. However, a recent study has led to a novel paradigm for the CdtB function distinct from its DNAse I activity: CdtB exhibits phosphatidylinositol 3-4-5 trisphosphate (PIP3) phosphatase activity in lymphocytes, which blocks PI-3 K signaling in lymphocytes, and results in toxin-induced cell cycle arrest and apoptosis [ 128 ]. In addition, blockade of the PI-3 K signaling has a pro-inflammatory effect, inducing the production of IL-1β, TNFα and IL-6 by macrophages [ 129 ].…”
Section: Introductionmentioning
confidence: 99%